High-efficient, manually-shapeable gamma- and X-ray shield – an introduction of paraffin-tungsten microcomposite along with its properties and recycling possibilities - Jolanta Sobczak; Adrian Truszkiewicz; Szymon Ruczka; Paweł Gancarz; Aleksandra Cyganiuk; Jacek Fal; Emil Korczeniewski; Marek Poręba; Krzysztof Cwynar; Marco A. Marcos; Javier P. Vallejo; Maciej Motyka; et al. (Materials & Design, 2025)
Today, it is hard to imagine modern medicine without X-ray machines or computed tomography scanners. Similarly, the energy industry would be incomplete without ecofriendly nuclear reactors, nor would advanced scientific research be possible without beam-based radiation tools. Unfortunately, both patients and operators are inevitably exposed to ionizing radiation found in all these environments, while widely used shields are often impractical, and their use carries many limitations. Therefore, new solutions with superior properties are needed in comparison to traditional options. Bearing this in mind, this paper presents a novel material – a composite based on paraffin and tungsten microparticles, which effectively protects against ionizing radiation and at the same time is easy to form with bare hands and could be recognized as nontoxic. The paper compares the characteristics of the attenuation of ionizing radiation by composites with different mass concentrations of tungsten particles for γ and X-rays. Because composites are distinguished by susceptibility in shape change, the rheological properties were experimentally determined along with other properties, vital in terms of industrial processes, such as thermal (including phase–transition temperatures), lubrication, and dielectric. Finally, recycling protocols have been developed to facilitate the recovery of individuals, tungsten particles and paraffin.